Penanganan Pastoral Burnout Berdasarkan 1 Raja-Raja 19:1-18 - Paulus Dimas Prabowo; Marchella Winda Sirang (STTII PURWOKERTO, 2023)
Servants of God are not immune to the threat of pastoral exhaustion in the life of ministry. Various pressures and challenges tempt His servants to be trapped in these affecting psychological conditions. One of the servants of God in the Bible who experienced pastoral burnout was Elijah, as recorded in 1 Kings 19:1-18. Jezebel's death threats after Elijah's spectacular ministry defeat hundreds of prophets of Baal, leaving her fearful, depressed, and irrational so she runs off to herself. But God brought restoration until finally Elijah returned to ministry. The purpose of this article is to describe how to handle pastoral burnout in God's servants based on Elijah's narrative in 1 Kings 19:1-18, using the thematic modeling analysis method. Through it, the results obtained that the handling of pastoral burnout on God's servants can be done with eight cars. First, by giving rest (vv. 5-6); second, with adequate food intake (vv. 5b-7); third, by providing a long pause (v. 8); fourth, by encouraging open speech (vv. 9, 10, 13 and 14); fifth, using a weak approach (vv. 11-12); because, by reminding of God's calling (vv. 15-16); seventh, by providing supportive partner services (v. 16); and awakens to the real reality (v. 18).